Does financial development contribute to SAARC׳S energy demand? From energy crisis to energy reforms. (January 2015) - Alam, Arif; Malik, Ihtisham Abdul; Abdullah, Alias Bin; Hassan, Asmadi; Faridullah,; Awan, Usama; Ali, Ghulam; Zaman, Khalid; Naseem, Imran
Abstract: SAARC members urgently need to secure sustainable energy supplies at affordable prices. Alarmingly high oil prices in the face of ever increasing energy demand have resulted in severe pressure on resources of SAARC members. The objective of this study examine the relationship among energy consumption, economic growth, relative prices of energy, FDI and different financial development indicators (i.e., broad money supply, liquid liabilities, domestic credit provided by banking sector and domestic credit to private sector) in the panel of selected SAARC countries namely Bangladesh, India, Nepal, Pakistan and Sri Lanka over a period of 1975–2011. Panel cointegration test suggest that the variables are cointegrated and have a long-run relationship between them. In addition, three different panel data methods i.e. pooled least square, fixed effects and random effects have been used to test the validity of the "energy-growth nexus via financial development" in the SAARC region. Specification tests (i.e., F -test and Hausman test) indicate that the fixed effect model considered as the best model to examine the relationship between energy and growth determinants, this implies that variables are apparently influenced by country effects only. The fixed effect model shows that there is a significant relationship among energy consumption, economic growth, FDI and financial development (FD) proxies, however, FD indicators has a larger impact on increasing energy demand, followed by GDP per capita and FDI. Therefore, it is concluded that there is a trade-off between the energy and growth variables in SAARC region, collective efforts is required to transform SAARC region from an energy-starved to an energy efficient region.